Baby names in Japan, 2019–2024: Common writings and their readingsOpen Science Framework - Yuji Ogihara (Data in Brief)
To conduct empirical research on Japanese names and naming practices, actual name data including both writings and readings are necessary. A previous report provided data on Japanese baby names born between 2004 and 2018. However, to examine temporal changes in names and naming practices and their underlying psychological/societal/cultural changes, it is necessary to add new data and update the database of names. Therefore, in this report, I provide new data on Japanese baby names born between 2019 and 2024. The methods are the same as those used for the previous dataset. The data include common writings of baby names and their readings, generated from annual surveys on baby names conducted by a Japanese private company. The data were collected under the same conditions over six years. This article will be useful for empirical research on Japanese names and naming practices.